Lamin A/C Haploinsufficiency Causes Dilated Cardiomyopathy and Apoptosis-Triggered Cardiac Conduction System Disease - Wolf, Cordula M (2007)
Mutations in the lamin A/C (LMNA) gene, which encodes nuclear membrane proteins, cause a variety of human conditions including dilated cardiomyopathy (DCM) with associated cardiac conduction system disease. To investigate mechanisms responsible for electrophysiologic and myocardial phenotypes caused by dominant human LMNA mutations, we performed longitudinal evaluations in heterozygous Lmna(+/-) mice. Despite one normal allele, Lmna(+/-) mice had 50% of normal cardiac lamin A/C levels and developed cardiac abnormalities. Conduction system function was normal in neonatal Lmna(+/-) mice but by 4 weeks of age AV nodal myocytes had abnormally shaped nuclei and active apoptosis. Telemetric and in vivo electrophysiologic studies in 10 week-old Lmna(+/-) mice showed atrioventricular (AV) conduction defects and both atrial and ventricular arrhythmias, analogous to those observed in humans with heterozygous LMNA mutations. Isolated myocytes from 12-month old Lmna(+/-) mice exhibited impaired contractility. In vivo cardiac studies of aged Lmna(+/-) mice revealed DCM; in some mice this occurred without overt conduction system disease. However, neither histopathology nor serum CK levels indicated skeletal muscle pathology. These data demonstrate cardiac pathology due to heterozygous Lmna mutations reflecting a 50% reduction in lamin protein levels. Lamin haploinsufficiency caused early-onset programmed cell death of AV nodal myocytes and progressive electrophysiologic disease. While lamin haploinsufficiency was better tolerated by non-conducting myocytes, ultimately these too succumbed to diminished lamin levels leading to dilated cardiomyopathy, which presumably arose independently from conduction system disease.